FENOMENA SOSIAL WANITA PENDAMPING KARAOKE TEMPAT HIBURAN MALAM PANTAI BIRA - Jahrir, Andi Sahrul; Adam, Arlin; Kamaruddin, Syamsu A (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research aims to describe the phenomenon of the existence of female karaoke companions at the Bira beach nightlife venue, Bulukumba Regency. This research uses qualitative methods with descriptive research type. Data collection in this research was carried out using interview techniques and observation. The results of this research discuss the existence of female karaoke companions based on their social identity, social motives and social roles. Based on the results of this research, theoretically it is hoped that it can become a source of information in enriching scientific insight and as reference material for further research, as well as contributing ideas for the author in the process of applying the knowledge that has been obtained, especially regarding the lives of female karaoke companions who work in nightclubs.